Diversity and philanthropy at African American museums : Black Renaissance - Banks, Patricia Ann (Abingdon, Oxon ; New York, NY : Routledge, 2019)
"Diversity and Philanthropy at African American Museums is the first scholarly book to analyse contemporary African American museums from a multifaceted perspective"--
Diverse patrons, diverse values -- African American/all-American -- Doing well by doing good -- The connoisseur's eye -- A new generation -- Rethinking cultural patronage in a diverse age.
OCLC-licensed vendor bibliographic record.
Keywords: African Americans -- Museums; Museums -- Social aspects -- United States; Cultural pluralism -- United States; Social classes -- United States; Social values -- United States; Philanthropists -- United States; Museums -- United States -- Endowments; BUSINESS & ECONOMICS / Museum Administration & Museology; REFERENCE / General; TRAVEL / Museums, Tours, Points of Interest; SOCIAL SCIENCE / Philanthropy & Charity